Global Marketing Management Training for Batik Craftsmen in Solo - Sisca Sisca; Andy Wijaya; Erbin Chandra; Hengki Mangiring Parulian Simarmata (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Batik has a high artistic value, which reflects the icon of Indonesian culture itself. As an ancestral heritage, Indonesian people continue to preserve batik to this day by maintaining the beauty of the colors and various patterns that are influenced by the characteristics of various regions. There is one city in Indonesia known as the city of batik, namely the city of Solo. Solo Batik Carnival or better known as SBC is one of the annual agenda of the Surakarta Tourism Office which is held in Solo with the main objective of introducing batik as a Javanese cultural heritage, and making Solo a fashion tourism destination. However, the lack of knowledge of global marketing management which has an impact on the potential for global competitiveness of batik SMEs has not been realized. In order to overcome the problems faced and help empower batik business people in Solo, it is necessary to increase knowledge about marketing strategies, especially in the global market. This service activity is carried out using training methods that are carried out online through zoom meetings for Batik Craftsmen in Solo. The results of the training showed that Solo Batik craftsmen after participating in global marketing management training experienced an increase in knowledge about marketing strategies, especially regarding global marketing which was quite good, which was shown through the feedback given during the training and the high interest in marketing their batik products abroad. in the future.